Isozyme markers and taxonomic relationships among Vigna species - Sonnante, G.; Piergiovanni, A.; Ng, N.; Perrino, P. (1997)
Isozyme markers are commonly used to study populations, taxonomy, and the genetics of crop species. In the genus Vigna. these markers have been investigated mainly to assess genetic diversity in the V. unguiculata complex. The aim of this study was to extend isozyme analysis to other sections of the genus Vigna. in order to evaluate their taxonomic relationships. Nine species of the sections Cariciitg,Vigna, and Plectotropis were tested. Interest in the selected species is high since they carry important traits, such as resistance to biotic and abiotic stresses, which are useful in cowpea breeding programs. For each species, several accessions of different geographical origin were analyzed. Isozyme data were statistically analyzed. Similarity was evaluated and a (JPGMA dendrogram was constructed. Very low levels of similarity were revealed among species, whereas variability among accessions differed within each species. In the section Vigna, V. luieola and V. marina were shown to be closely related, whereas the other species had a lower similarity. The V. unguiculata complex, which belongs to the section Catitmg, formed a separate group when compared to the other species, although it was closest to V. vcxillata.